High‐Resolution Monitoring of Controlled Water Table Variations From Dense Seismic‐Noise Acquisitions. Issue 8 (11th August 2022) - Gaubert‐Bastide, T.; Garambois, S.; Bordes, C.; Voisin, C.; Oxarango, L.; Brito, D.; Roux, P.
Abstract: Water‐resource management has become a major global issue in a world threatened by climate change. High‐resolution geophysical methods may be of valuable help in monitoring the water masses, both in space and time. Passive seismic interferometry takes advantage of ambient seismic noise to recover the variations in seismic wave velocity induced by changes in groundwater. We present hereafter the time and space monitoring of an hydraulic dome artificially formed to prevent biological and chemical pollutants from entering the exploitation field of Crépieux‐Charmy (Lyon, France). We use a dense seismic network to passively monitor the water table changes induced by infilling of an infiltration basin at the water supply facility for the two million inhabitants of the Lyon Metropolis (France). We assess the hourly seismic velocity variations over 19 days, during which two filling and drainage cycles were performed. The use of a dense three‐component seismic network allows fine characterization of the seismic wavefield, and offers the possibility to include the analysis of 4, 851 raypaths in a robust inversion algorithm based on ray theory. The velocity variations are mapped with high resolution. They are directly related to the water table variations and to residual water saturation changes within the unsaturated zone. This seismic experiment highlights the three‐dimensional (3D) implementation and evolution of a hydraulic dome under the infiltration basin. This dynamic information helps in the understanding and modeling of water flows between the water table and a river, which represents a fundamental issue for discussions on the effectiveness of the barrier. Plain Language Summary: Monitoring aquifers becomes a crucial necessity to keep the water resource safe and sustainable, especially in water catchment fields which are usually located in proximity of urban areas. Passive seismic interferometry, which takes advantage of the continuous ambient seismic noise signals, can provide access to the properties and evolution of the water table with a noticeable spatial resolution. Here, we propose the use of a dense seismic network to monitor water content changes, artificially generated by controlled infilling/drainage cycles of a basin originally designed to mitigate potential pollution of the water field from surrounding rivers. The analysis of waves propagating within the network allows us to obtain hourly time‐lapse seismic velocity variation maps with high resolution. It notably highlights the shape of a water dome that appears (or disappears) when filling (or emptying) the basin, but also that seismic variations are sensitive to both water table and water content variations occurring within the vadose zone. This study eventually shows that the seismic‐noise based method can provide relevant information on fluid flow variations and pragmatically on the effectiveness of the infiltration basin to protect the water field from potential pollution. Key Points: The use of a dense seismic network allows us to obtain high resolution dynamic maps of water content changes through a tomography process The space and time evolution of an hydraulic dome artificially formed under an infiltration basin is highlighted The obtained seismic velocity variations are sensitive to the water table fluctuations and to residual water saturation changes within the unsaturated zone